Transformasi Digital Perbankan Syariah: Strategi Menjaga Stabilitas Dan Relevansi Di Era Fintech Global - Khaidar rahmaini jamila; Adelia Safitri; Alya Arianti Nasution; Indah Tri Sari Harahap (CV. ITTC INDONESIA, 2025)
Advances in digital technology are supporting significant changes in the Islamic banking industry globally. Fintech innovations influence service patterns, business models, and customer expectations for speed and ease of transactions. This study aims to explain the implementation of digitalization in Islamic banking operations, strategies to maintain stability through digital transformation, and its role in maintaining relevance amid global fintech competition. The method used is descriptive qualitative using a literature analysis approach and several documents. The results show that digitalization increases the level of service efficiency, strengthens risk management, and supports product innovation according to sharia principles. Digital transformation also contributes to maintaining financial system stability as well as increasing the reach of service inclusion. These findings confirm the need for a planned and sustainable digital strategy for Islamic banking. This effort encourages competitiveness, public trust, and the application of the Islamic financial industry in the global economic environment dynamically as well as competitively and sustainably in the future.